SOSIALISASI PENCATATAN AKUNTANSI HIJAU DAN PENGELOLAAN DANA CSR PADA USAHA AYAM PETELUR KELOMPOK TERNAK PATUH ANGEN - Muhammad Syukri; Syarifah Massuki Fitri; Suandi Suandi (LPPM Institut Pendidikan Nusantara Global, 2025)
This community service activity was carried out with the aim of improving the understanding and skills of members of the Patuh Angen Livestock Group in Batu Kumbung Village, Lingsar District, in implementing green accounting records and CSR fund management in the laying chicken business. Through direct socialization and training methods, this activity introduced the importance of recording environmental costs such as waste, water use, and environmentally friendly feed, as well as how CSR funds can be managed transparently and contribute to sustainable development. The results of the activity showed an increase in participants' knowledge of green accounting and awareness of the importance of reporting CSR funds. However, several obstacles faced include limited technical skills in financial recording, minimal access to digital recording technology, and lack of local policy support related to environmentally friendly practices. Based on these findings, it is recommended that there be a follow-up mentoring program, the preparation of a simple green accounting module based on the needs of farmers, and the active involvement of the village government and related agencies in encouraging environmentally-based regulations and incentives.